L'intensità dell'uso del suolo e la sua evoluzione attraverso i dati statistici: metodologie per un'analisi diacronica - Ciccacci, Marco; Lombardo, Giovanni; Sabbi, Alberto; Salvucci, Gianluigi (GEOmedia, 2017)
In the hypothesis of wanting to economize the consumption of land, applying to this aim a reasoning based on the exhaustibility of this resource, it is appropriate that it increases the intensity of use within the limits of the achievement of carrying capabilities (load capacity), which the portion of territory can support. The informative heritage offered by Istat is certainly valuable, as in the division of the territory into sections of Census is able to show changes in land use nationally. In fact, the allocation of variables detected in the various censuses, in reference to the minimum territorial unit, are able to qualify with measurable data concepts of urban areas rather than industrial or rural. In this respect, ISTAT classifies Census sections in four types which can be considered a great many broad categories of land use. In particular, this study proposes an analysis of the changes shown by the location of the town, which corresponds a higher population density. The methodology used by ISTAT for the demarcation of the resort towns starts from the observation of aerial photos, identifying areas containing buildings which are separated by a distance not exceeding 70 meters. Among the different types of evolution that occurred in residential areas, some are attributable exclusively to the improvement of the resolution of the material, so will be assessed properly the "convoluted" from the center of town to the other "lower-ranking". By overlapping sections used in censuses from 1991 to 2011, we obtain the expansion of urban previous polygons, which are attributed to the socio-demographic characteristics found in this survey. This procedure must be carefully evaluated before making the various comparisons, in order to avoid possible errors. In this preliminary study, we present some rough calculations, and critical cases that are going to develop in later works.